Mid-infrared optical valve based on VO_{2} - Antonio García-Martín; Raquel Álvaro; Zhuoqun Fang; Alexandre Zimmers; Zhuoying Chen; Lionel Aigouy (Physical Review Research)
We demonstrate an efficient optical binary-switch effect in nanoslit arrays achieved via the temperature-induced phase transition of VO_{2}. Experimental measurements reveal a polarization-dependent 60% reduction in reflectivity during the insulator-to-metal transition. Tuning a single parameter of the slit enables control over the “optical-valve” effect. Full numerical simulations support these findings, predicting a reflectivity reduction up to 90%. The nearly one-to-null transition in reflectivity mimics the operation of a digital switch, with the high-reflectivity and the low-reflectivity states providing a binary response much like digital electronics.